A study on creating games and virtual worlds from a software engineering perspective - Tee, Mark Kit Tsun (2011)
The industry of developing games and virtual environments have come a long way, but it is not without its share of problems. In many ways, virtual worlds entail similar development processes as games, as they both require expertise from creative and technical facets. While facing similar difficulties as other commercial projects, creating games presents its own unique challenges due to its multi-disciplinary nature. Because of this, beginner and indie developers face complications in attempting to apply Software Engineering methods (which are efficiently tailored to guide general software projects) to reduce the chance of project failure. This study aimed to examine the construction of games and integrate it into the Software Process. First, the background of game development and Software Engineering were explored, deriving the introductory guides for both. Then, a guidelines draft is developed to offer advice on grafting aspects of the Software Process onto existing game or virtual world projects. They are aimed at independent developers as they represent the future workforce of the game development industry. To test the draft, an experimental project is carried out using the guide as a supplementary resource. The project resulted in a 3D action-RPG game platform that can be used as a starting point for advanced feature placement and content development. It demonstrated that the guidelines were educative but lacks depth and correctness. Revisions on these guidelines will transform it into a stepping stone resource that introduces novice game developers to integrating Software Engineering processes and practices into their projects. (Abstract by author)